PENERAPAN ASUHAN KEPERAWATAN PADA USIA LANSIA DENGAN MASALAH NYERI LUTUT MELALUI INTERVENSI LATIHAN STRETCHING DI RT 001 RW 009 KEBON BAWANG JAKARTA UTARA - Rifah Miladdina, (2022)
Knee pain is a disorder of the musculoskeletal system which includes the patella bone, joints, and soft tissues. Stretching is a simple activity that is done to improve muscle stiffness or tension to make it more relaxed. This application has a purpose, namely to determine the effectiveness of the application of stretching exercises to reduce knee pain in the elderly in Rt 001 Rw 009. The subjects in this study were two elderly people with knee pain problems, consisting of 1 managed patient and 1 resume patient. The level of knee joint pain was measured using the VAS (Visual Analogue Scale) pain scale before and after the intervention was given for 6 meetings in 2 weeks. The result of this study is that there is a decrease in the pain scale in both managed patients and resume patients. The conclusion in this study that stretching exercises can affect the reduction of knee pain scale. Keywords : elderly, stretching exercise, knee pain.